2017
DOI: 10.1101/122416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiology and antimicrobial resistance characteristics of the ST131-H30subclone among extraintestinalEscherichia colicollected from US children

Abstract: Summary: ST131-H30 was responsible for 5.3% of all extraintestinal E. coli infections and 43.3% of ESBL-producing extraintestinal E. coli infections among US children. The clinical and demographic correlates of infection with ST131-H30 differed between extended-spectrum cephalosporin-resistant and -sensitive isolates. Corresponding author (pre-publication):Arianna

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It has been shown that the E.coli ST131 clone, which has become the most common extraintestinal pathogenic E. coli clone circulation today by colonizing the gastrointestinal systems of humans and food animals, is associated with ESBL production, mostly CTX-M-15, as well as multidrug resistance and treatment failure. 4,7 Among the identified subclones of ST131, H30R shows resistance to fluoroquinolones; H30Rx, on the other hand, is characterized by the production of CTX-M-15-type ESBL and members of this subclone are resistant to broad-spectrum cephalosporins, as well as fluoroquinolones. 8,9 The detection of high-risk ST131 clone in a population provides important information on the dynamics of spread of resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the E.coli ST131 clone, which has become the most common extraintestinal pathogenic E. coli clone circulation today by colonizing the gastrointestinal systems of humans and food animals, is associated with ESBL production, mostly CTX-M-15, as well as multidrug resistance and treatment failure. 4,7 Among the identified subclones of ST131, H30R shows resistance to fluoroquinolones; H30Rx, on the other hand, is characterized by the production of CTX-M-15-type ESBL and members of this subclone are resistant to broad-spectrum cephalosporins, as well as fluoroquinolones. 8,9 The detection of high-risk ST131 clone in a population provides important information on the dynamics of spread of resistance.…”
Section: Introductionmentioning
confidence: 99%